Usability of vegetable extracts in the protection against Alternaria alternata - Tóth, Csaba Tamás; Csubák, Mária (Acta Agraria Debreceniensis, 2012)
In our country, wormwood ragweed (Ambrosia artemisiifolia) may cause serious problems. Nearly 5 million hectares of agricultural area was infected with ragweed (Ambrosia artemisiifolia), which is believed useless weed. Allergological point of view, most problematic weeds adventive. However, many physiologically very beneficial compound also included, those with the effects have been known also by the Indians. On this basis, herbs can be thought of as ragweed. Our goal was to present that the ragweed contains antifungal active substances as well. In this paper we tested the biological activity of the extracts against Alternaria alternata F.00750 in vitro. We related based on our examination that ragweed contains biologically active agents, by which it is hampered the reproduction of the Alternaria alternata. The minimum effective concentration was 300 mg extract in a Petri dish, which was three days inhibited the growth of fungus. Full fungicidal effect was observed over dose 525 mg.